IVAN PAVLOV'S BEHAVIORISTIC PERSONALITY THEORY IN LEARNING SHAPES THE BEHAVIOR OF LEARNERS - Nabilaa Faizatuz Zuhriyah; Vivi Meilinda; Saona Saona; Rani Santika; Nuralifah Nuralifah (Publikasi Indonesia, 2023)
One of the schools of psychology that can increase the effectiveness of learning is behaviorism. by using Ivan Pavlov's theory of behaviorism in teaching to influence student behavior. The purpose of this research is to increase the efficacy and efficiency of learning. This research uses literature review or literature research strategy. Research journals, theses, textbooks, and publications related to the issues being discussed are sources of research data. Based on the data analysis, it was found that: Behaviorism is a learning theory that prioritizes training or habituation in the learning process and emphasizes aspects of behavior formation, including stimuli and responses that can affect changes in behavior as a learning outcome